Malocclusion and quality of life in adolescents - Sively, Mercado (2018)
Malocclusions are buccodental alterations of multiple etiology. According to the World Health Organization occupy the third place of prevalence within oral health problems, which makes them of great importance. They will not only affect oral functionality and aesthetics in the person, but also influence the psychosocial aspect. Everything that exists as a consequence of the quality of life of each person is affected. The objective of this literature review is to show how the qua lity of life has been altered by malocclusions.